Representasi Perempuan Berdaya Pada Akun Instagram @Ciledugfemalecommunity - Permata, Sandy; Kencana, Woro Harkandi; Bahriyah, Euis Nurul (Lembaga Penerbitan Universitas Esa Unggul, 2026)
The development of social media, especially visual-based platforms like Instagram, has changed the way women construct their identities, including through virtual women's communities. This study examines the representation of empowered women on the Instagram account @ciledugfemalecommunity, a community of women residing in the Ciledug area and its surroundings. The methodology used is a qualitative approach with content analysis methods to analyze the themes, visuals, and narratives in the account's bio, photos/videos, and captions. This study shows that empowered women are represented in three dominant main themes: women as drivers of local communities, women as subjects of